Long-term evaluation of the impact of urbanization on native and non-native fish assemblages - Shubha N. Pandit; Mark S. Poesch; Jurek Kolasa; Laxmi Koirala Pandit; Jonathan L. W. Ruppert; Eva C. Enders (Aquatic Invasions)
Urbanization often leads to the homogenization of species composition in aquatic ecosystems, as it introduces disturbances that can destroy the habitats of unique endemic or native species while creating alternative habitats for species capable of adapting to these conditions. This study utilized a long-term dataset from 1971 to 2010, focusing on fish species presence within three watersheds of the Greater Toronto Area, Canada. The objective was to evaluate any changes in fish communities over time across three groups of species assemblages: native, non-native species, and a combining of all species. We considered key predictor variables for which data exist: catchment area, distance to a species pool source (Lake Ontario), and percentage of urban cover, to determine their impacts on species richness over time. Three hypotheses were tested: (1) the rate of change in species richness differs among the three groups; (2) urbanization promotes the spread and homogenization of non-native species distribution; and (3) native species assemblages exhibit high nestedness initially, decreasing over time as non-native species established and replaced native species. We used general linear models and the nestedness analysis to characterize matrices of species distributions of native and non-native fish assemblages among the catchments over time. Overall, the results indicate that nestedness temperatures (NTs) for native fish were lower compared to non-native fish assemblages. Over the four decades studied, native species richness declined with increasing urban cover, while non-native species richness increased and compensated for native losses. Furthermore, native species assemblages exhibited high nestedness at the beginning of the record period, which decreased over time as non-native species became established and replaced native species. This trend suggests that further changes in fish communities are probable. As native fish communities become patchier (not nested), this process may accelerate, potentially isolating communities and making them more prone to perturbations.